Implicature Analysis Of Song Lyrics In Wave To Earth’s Playlist - Fatiha Nadine Cantika; Nurul Fadhillah, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The text discusses the concept of Implicature, which is the implied meaning of an utterance that goes beyond what the speaker literally says by George Yule’s Theory (1996). The text aims to show how implicature enriches the communication between humans and makes language more expressive and interesting. The text provides an explanation of the various Implicatures, such as Conversational, Conventional, and Scalar Implicature. This research using the descriptive qualitative method is employed by understanding through out lyrics. The text also gives examples of how Conversational implicature is used in wave to earth’s song lyrics, to analyze the Generalized Conversational Implicature (7) and Particularized Conversational Implicature (2) which has been sorted in some playlist. Therefore, the data was chosen from the wave to earth song playlist and various sources, including Google, YouTube, and Spotify.